Roland Barthes' Semiotic Analysis Of The Wicked Film Poster: A Study Of The Meaning Of Denotation, Connotation, And Myth - Naufal Budiman; Azana Rahma; Putri Rizky Ramadhani; Lia Nur Amaliah; Mulida Isfandiawaty; Mayang Pipit (International journal of technology and education research, 2026)
A film poster is a visual communication medium that not only functions as a promotional tool but also as a sign system containing various cultural and ideological meanings. This study aims to analyze the meaning contained in the Wicked film poster using Roland Barthes' semiotic approach through three levels of meaning: denotation, connotation, and myth. This study uses a qualitative descriptive method with documentation techniques on one object, namely the official Wicked film poster. Analysis was carried out on visual elements such as characters, colors, lighting, composition, background, typography, and slogans on the poster. The results show that at the denotation level, the poster displays two main characters with contrasting visual characteristics, a yellow road leading to the castle, and a strong fantasy nuance. At the connotation level, this visual contrast represents moral conflict, identity struggles, hope, and the process of character transformation. Meanwhile, at the myth level, the poster constructs an ideology about the dichotomy between good and evil, transformation as a path to redemption, fantasy as an emotional escape, and Western cultural constructions that associate beauty with goodness and physical differences with moral deviance. This study shows that film posters not only convey information about a film but also reproduce social and cultural values ​​that exist in public spaces through a visual sign system. Thus, Roland Barthes's semiotics provides an effective analytical framework for uncovering the explicit and implicit meanings hidden in contemporary visual media.